0106 The Role Of Encoding Strength In The Prioritization Of Memories For Consolidation During Sleep. (27th April 2018) - Denis, D; Bursal, V; Oquin, S; Morgan, A; Stickgold, R
Abstract: Introduction: A large body of evidence has shown that sleep plays an important role in the consolidation of declarative memory. More recently, it has been suggested that the brain prioritizes certain memories to be consolidated over others. The mechanisms underlying this remain unclear. This study investigated the role initial encoding strength may play in the selection of memories that undergo consolidation. Methods: Participants learnt unrelated word-pairs to 3 different levels of encoding. Encoding strength was manipulated by the number of times each word-pair was presented. Following learning, an immediate free-recall proceeded where participants saw the first word of each pair and had to recall the second word. Then, half the participants (n = 20) returned for a delayed test 12 hours later (constituting a wake group), with the other half (n = 20) returning 24 hours later (constituting a sleep group). Results: At immediate test, the three levels of encoding were all significantly different from each other, with the items in the weakest condition being remembered the poorest, and items in the strongest condition being remembered best. There were no differences in immediate recall performance between the sleep and wake group. At delayed test, it was found that the 24-hour group showed less forgetting across all encoding strength conditions compared to the 12-hour group (p = .007), suggesting a general beneficial role of sleep on delayed test performance. Furthermore, a significant group x encoding condition interaction showed that, in the 24-hour group, there was significantly less forgetting for the most weakly encoded items compared to the other levels of encoding (p = .035). Conclusion: These results suggest that sleep is important for the consolidation of declarative memory, and the brain prioritizes those items that are weakly encoded over those that are strongly encoded. Support (If Any): NIH grant MH044832.